Kilka uwag na temat miejsca badań ilościowych w polskiej historii gospodarczej. Stan i perspektywy - Matera, Rafał (Roczniki Dziejów Społecznych i Gospodarczych, 2015)
Some remarks on the place of quantitative research in Polish economic history. The state and prospects (Summary) The article is a polemic on the text by Piotr Guzowski and Radosław Poniat entitled: The place of quantitative research in modern Polish historiography, which appeared in 2013 in the 73 volume of Roczniki Dziejów Społecznych i Gospodarczych [The Yearbook of Social and Economic History]. The article refers to a number of hypotheses and opinions presented by scholars who offered a critical analysis of the state of Polish economic history, the methods it uses and the scholarly potential it has. The article aims to present dilemmas faced by scholars specializing in economic history – one which rests on two pillars: history and economy. The author posits that economic history (not only in Poland), in exploring new ways of development, continues to rely both on a traditional history, known for its adherence to idiographic methods (which does not rule out the selection and juxtaposition of different data), and on contemporary economics, concerned mainly with model-building. The author argues for adopting a methodologically open approach to economic history, discussing a number of significant, both western and Polish, publications on this issue. The article also contains a review of the use of quantitative methods in Polish economic history.